Faktor - Faktor yang Mempengaruhi Kualitas Konsumsi Pangan Rumah Tangga Penerima Program Pekarangan Pangan Lestari (P2L) Kota Pekanbaru Provinsi Riau - Purwati Purwati; Elinur Elinur; Hamdi Agustin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The score of the expected food pattern, the quantity, variety, and quality of food consumed, can be used to assess a person's eating quality. The fact that Pekanbaru City's PPH score for 2020 is only 84.7 points below the optimal value demonstrates that its citizens' food consumption is not yet varied and nutritionally balanced. This study examines PPH scores for household food consumption among P2L participants and elements that affect the caliber of food consumed in P2L-participating families. This study used a survey methodology, with the respondent number being 65-person total sample chosen via stratified random selection. Analysis of PPH scores for household food consumption in P2L participants used descriptive statistics. In contrast, inferential statistics and multiple linear regression are used to analyze the variables that affect the P2L household food intake PPH score. The results showed that the P2L participant's household food consumption PPH score was 85.4. P2L program increases PPH score in Pekanbaru. The P2L household food consumption PPH score is primarily influenced by age, educational attainment, and family size.